An Analysis of Implicature Forms and Functions in the Film Ajari Aku Islam - Neldi Harianto; Nurfitri Susanti; Anggi Triandana; Sahrizal Vahlepi (Titian: Jurnal Ilmu Humaniora, 2021)
This research aimed to express the implicature of forms and functions in the film Ajari Aku Islam. This research used descriptive qualitative research. The source of the research was the utterances among the characters in the film Ajari Aku Islam. The data were collected by listening and taking notes technique with advanced method of uninvolved conversation observation technique.The finding of the research in this film that the researcher found conventional and conversational implicatures. The forms of conversational implicature in this research was revealed through violation of the cooperative principle which included: a) the quantity maxim violation, b) the quality maxim violation, c) the relationship maxim violation, and d) the way maxim violation. Next, the functions of the implicature in the film Ajari Aku Islam were: a) the function of implicature in directive speech act, b) the implicature function in expressive speech act, c) the implicature function in assertive speech act, d) the implicature function in commissive speech act, and e) the function implicature in declarative speech act. Between conventional and conversational implicature, conversational implicature was more dominant. Likewise the maxim violation and the function implicature, both were equally dominant.